Analisis Kontingensi pada Jaringan Transmisi 150 kV Subsistem Sulawesi Selatan Menggunakan Power World Simulator - Briliant Noviansel; Jumadi Mabe Parenreng; Al Imran (International Forum of Researchers and Lecturers, 2026)
The reliability of the electrical power transmission system greatly determines the continuity and quality of power distribution. This study aims to analyze the reliability level of the 150 kV transmission system through a contingency study (N-1) using the Performance Index (PI MVA) method and voltage profile evaluation. The theoretical study is based on the concepts of power flow, thermal loading limits of lines, electrical power system safety criteria, and the performance index method as an indicator of the critical level of a line. The research method used is a descriptive quantitative method with simulation using PowerWorld Simulator software. Data were obtained from system parameters, line loading data, and simulation results under normal and contingency conditions. The results show that most buses have voltage profiles within the standard range of 0.95–1.05 pu. PI MVA calculations indicate that most lines have PI values < 1 (safe), but some lines, such as TBNGA–PNGYA and GIS BNTALA–TBNGA, have PI > 1, indicating overload conditions. Overall, the system remains stable, but attention is needed on lines with the highest indices to improve system reliability.